IoT Enabled Headband for Social Distancing - Santhosha Rao (International Journal of Advanced Science and Technology, 2020)
The worldwide outbreak of COVID-19 has deeply changed the way we interact with each other. It is essential to practice social distancing measures in our day to day life. As countries are looking at how to resume business activities after exiting from lockdown, maintaining social distancing measures are gaining importance in the minds of the people. It is really a challenging task for the organizations to enforce social distancing guidelines. The technological advancements in the field of Internet of Things (IoT) should be exploited in designing a cost-effective wearable device which enforces social distancing measures. In this work, a low cost IoT enabled headband is designed which generates alerts in case of social distancing violation besides sending IFTTT notifications. The notifications help the organizations in designing their social distancing enforcement strategy.